The cancer wellness cookbook : smart nutrition and delicious recipes for people living with cancer - Mathai, Kimberly (Seattle : Sasquatch Books, 2014)
'Whether you are a cancer patient undergoing treatment, a caregiver, or a survivor, you'll find this cookbook and nutritional guide essential--it includes the latest scientific research on improving the lives of people living with cancer. Created by Seattle's Cancer Lifeline, The Cancer Wellness Cookbook features nutritional plans and 100 recipes focusing on the foods that have been shown to prevent and forestall the spread of cancer. With super healthy and delicious ingredients like berries, mushrooms, beans, tomatoes, and fish, these dishes taste great and are filled with the nutrients that aid a person undergoing chemotherapy and other cancer treatments'--
Includes bibliographical references (p. 227-233) and index.
Keywords: Neoplasms -- diet therapy -- Popular Works; Neoplasms -- Diet Therapy -- Cookbooks; Neoplasms -- Prevention & Control -- Popular Works; Neoplasms -- Prevention & Control -- Cookbooks; Nutrition Therapy -- Popular Works